Study on the Effect of Foundation Pit Excavation on the Deformation of Adjacent Shield Tunnel - Cirong Lu; Long Huang (Advances in Civil Engineering)
With the construction of a large number of urban infrastructures, there will be new engineering loading and unloading behavior around the urban metro built-up area, and the deformation characteristics of the new tunnel will be more significantly affected by the external environment. In this paper, the damage to shield tunnel structure caused by pit excavation in similar engineering is analyzed. The finite element model, based on the different distances between the foundation pit and the tunnel and the different thicknesses of tunnel segment, is established. The displacement field and the convergent and longitudinal deformation of the shield tunnel segment with different thicknesses are analyzed. The following conclusions are drawn: (1) the excavation of adjacent foundation pit will cause excessive displacement, settlement, and structural convergent deformation of shield tunnel, causing structural damage such as increasing of faulting, water leakage, and seeping. (2) With the decrease of the distance between the tunnel and the foundation pit, the convergent deformation of the tunnel increases continuously, and when the distance is less than 30 m, the increase of segment thickness greatly improves the convergent deformation of the structure. (3) The increase of segment thickness has no obvious effect on the resistance to longitudinal deformation. When the distance between tunnel and foundation pit is less than 50 m, additional protective measures should be taken to reduce the longitudinal deformation of tunnel.